2012
DOI: 10.1161/strokeaha.111.639427
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Attenuates Infarct Volume, Mitochondrial Dysfunction, and Matrix Metalloproteinase-9 Induction After Focal Cerebral Ischemia

Abstract: Background and Purpose Asiatic acid (AA) has been shown to attenuate cerebral infarction in a mouse model of focal ischemia and shows promise as a neuroprotective stroke therapy. To facilitate translation of these findings to clinical studies, we determined pharmacokinetics, a dose response relationship, the therapeutic time window, and efficacy using multiple stroke models. We also explored potential mechanisms of action. Methods Escalating doses of intravenous AA were administered and serum concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…It may mediate neuroprotection by protecting mitochondria and inhibiting matrix metalloproteinase-9 induction and activation. 12) The current study has confirmed efficacy in a rat model of embolic focal cerebral ischemia. Most animal stroke models were developed to induce cerebral ischemia within the MCA territory with the intent of mimicking a common clinical scenario.…”
Section: )supporting
confidence: 66%
See 2 more Smart Citations
“…It may mediate neuroprotection by protecting mitochondria and inhibiting matrix metalloproteinase-9 induction and activation. 12) The current study has confirmed efficacy in a rat model of embolic focal cerebral ischemia. Most animal stroke models were developed to induce cerebral ischemia within the MCA territory with the intent of mimicking a common clinical scenario.…”
Section: )supporting
confidence: 66%
“…12,14) Each item was graded from 0 (severe deficit) to 3 (no deficit). The grading of all 6 items was added.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has protective effects against neurotoxixity. These effects of AA have been shown in stroke and some degenerative neurodisorders such as Parkinsonism and Alzheimer Disease (7,10,12).…”
Section: Interleukin 1βmentioning
confidence: 98%
“…Some reports stated that AA is a promising agent in the treatment of stroke. AA exerts neuroprotection by maintaining the stability of the blood brain barrier and by protecting the mitochondrial functions (10,12,13,20).…”
mentioning
confidence: 99%